Sooner than you think : neural interfaces are finally here (O'Reilly Media, 2019)
"During the past decade, significant advancements in artificial intelligence and machine learning have expanded how we communicate and interact with the world. There are more screens and devices in our lives, but our ability to control these devices hasn't kept pace. While controversial projects involving invasive brain-machine interfaces have been grabbing headlines, this technology is still decades away from exiting the lab and changing how we interact with the digital world for the better. Patrick Kaifosh outlines a future where we'll be looking up at the world instead of down at our phones."--Resource description page